2023
DOI: 10.1136/gutjnl-2023-330168
|View full text |Cite
|
Sign up to set email alerts
|

Compared to histamine-2 receptor antagonist, proton pump inhibitor induces stronger oral-to-gut microbial transmission and gut microbiome alterations: a randomised controlled trial

Jiaying Zhu,
Chuqing Sun,
Min Li
et al.

Abstract: ObjectiveWe aim to compare the effects of proton pump inhibitors (PPIs) and histamine-2 receptor antagonists (H2RAs) on the gut microbiota through longitudinal analysis.DesignHealthy volunteers were randomly assigned to receive either PPI (n=23) or H2RA (n=26) daily for seven consecutive days. We collected oral (saliva) and faecal samples before and after the intervention for metagenomic next-generation sequencing. We analysed intervention-induced alterations in the oral and gut microbiome including microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…A number of interventional and observational studies have suggested that long‐term PPI use is associated with alterations in the abundance and diversity of various microbial species 16,29–32 . Consistent with our findings, a study based on 1827 healthy twins showed that PPI use was negatively associated with 22 OTUs from the Firmicutes phylum and positively associated with 20 OTUs from the Bacteroidales order.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A number of interventional and observational studies have suggested that long‐term PPI use is associated with alterations in the abundance and diversity of various microbial species 16,29–32 . Consistent with our findings, a study based on 1827 healthy twins showed that PPI use was negatively associated with 22 OTUs from the Firmicutes phylum and positively associated with 20 OTUs from the Bacteroidales order.…”
Section: Discussionsupporting
confidence: 90%
“…This was in line with our findings that PPI users had a lower abundance of Firmicutes and a higher abundance of the Bacteroidetes phylum 29 . PPI use could induce oral bacteria to colonize the gut by reducing the acidity of the stomach 16,32 . A recent randomized clinical trial (RCT) indicated that PPIs could cause a higher extent of oral‐to‐gut transmission and promote the growth of certain oral species in the gut compared to H2 receptor antagonists (H2RAs), a less potent acid suppressor, and subsequently have a more pronounced effect on disrupting the gut microbiota 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were (1) having MG signs and symptoms, such as muscle weakness and fatigue, and symptom fluctuation; (2) being seropositive for autoantibodies; (3) abnormal repetitive nerve stimulation or single-fiber electromyography; and (4) undergoing follow-up for ≥ 6 months from baseline. The exclusion criteria were (1) receiving aggressive immunomodulation therapy, including plasmapheresis, intravenous immunoglobulin, or rituximab, in the previous year or during the study inclusion period; (2) receiving antibiotics, probiotics in the previous 6 months; (3) having digestive disorders necessitating the use of a proton pump inhibitor or histamine-2 receptor antagonist, and disorders that related with change fecal microenvironments, such as inflammatory bowel disease in the previous year [20] , [21] ; or (4) requiring no immunosuppressant dose adjustment in the past one year. This study was approved by the Research Ethics Committee of Fu-Jen Catholic University Hospital (approval number: FJUH109042).…”
Section: Methodsmentioning
confidence: 99%
“…The use of acid suppressants, for example, proton pump inhibitors, elevates the gastric pH to over 6, which encourages the growth of gastric microbes. 14 Additionally, throughout the Correa's cascade of gastric carcinogenesis which is mainly triggered by H. pylori, increased infiltration of inflammatory cells and displacement of normal glandular tissue by metaplastic glands can eventually lead to the occurrence of neoplastic tissues in the stomach. 15 Thus, gastric pH increases while pepsin level decreases, enabling the expansion and alterations of microorganisms in the stomach.…”
Section: Gastric Microbial Dysbiosis In Gastric Carcinogenesismentioning
confidence: 99%